Combining Shell and GBT‐based Finite Elements – the Best of Both Worlds?. Issue 4 (14th September 2022) - Manta, David; Gonçalves, Rodrigo; Camotim, Dinar
Abstract: A general and efficient approach to model thin‐walled members and frames with complex geometries (including tapered and perforated members) is proposed, combining standard shell and GBT‐based (beam) finite elements. Each element type is employed where it is most effective: (i) shell elements in plastic and geometrically complex zones, and (ii) GBT elements in prismatic and elastic zones. After providing a brief overview of the finite elements employed, several illustrative numerical examples are presented and discussed, in order to show the capabilities and potential of the proposed approach – they concern linear static, bifurcation (linear stability – calculation of buckling loadings and mode shapes), vibration (calculation of natural frequencies and vibration mode shapes), dynamic and first‐order plastic zone analyses. These numerical examples involve members with tapered segments and/or perforations and frames with complex joint geometries. For validation and comparison purposes, full shell finite element results are provided – in all cases, an excellent match is obtained.